Development of biopolymer-poly(3,4-Ethylenedioxythiophene) based thin films and the potential for mercury ion detection using surface plasmon resonance - Md Ramdzan, Nur Syahira (2021)
The global issue caused by agricultural and industrial waste products has driven researchers to develop heavy metal ion sensors for the detection of water pollution. There are numerous works on the development of sensing layers involving different types of materials. Apart from the novelty of material, the effectiveness and efficiency of materials as sensing layers also should be emphasized. Therefore, this works aims to incorporate the biopolymer and conducting polymer materials with surface plasmon resonance sensors for better sensing properties toward heavy metal ions. This thesis suggests two different sensing thin films, chitosan/poly(3,4-ethylenethiophene) (Cs/PEDOT) and nanocrystalline cellulose/poly(3,4-ethylenethiophene) (NCC/PEDOT) for the detection of mercury ions. The structural properties of both thin films were confirmed by Fourier transform infrared (FTIR) spectroscopy by the presence of functional groups of the composites. Moreover, the atomic force microscopy (AFM) shows that the roughness of thin films increased for Cs/PEDOT and NCC/PEDOT thin films, which shows that the surface roughness is influenced by the presence of chitosan and nanocrystalline cellulose. Meanwhile, the optical properties of synthesized thin films were investigated using ultraviolet-visible (UV-Vis) spectroscopy where the absorbance peaks for the thin films can be observed at a wavelength around 220–700 nm. Based on the band gap energy analysis, the values obtained for both thin films are 4.093 eV and 4.082 eV for Cs/PEDOT and NCC/PEDOT thin films, respectively. Next, the proposed thin films have been incorporated with a surface plasmon resonance sensor (SPR) to evaluate the effectiveness and efficiency of sensing mercury ions in an aqueous solution. For Cs/PEDOT thin film, the detection performance showed the sensitivity of 21.9607° ppm–1 and the binding affinity constant value of 204.4990 ppm–1. Meanwhile, the NCC/PEDOT thin film showed higher sensitivity of 48.5193° ppm–1 and the Langmuir isotherm model yielded a higher binding affinity constant with values of 211.8644 ppm–1. The results indicate NCC/PEDOT thin film has a better sensing property compared to Cs/PEDOT thin film in detecting mercury ions. In conclusion, this work has successfully developed a new sensing layer in fabricating an effective and potential heavy metal ions sensor.